The interannual variability of the eddy kinetic energy in the Banda Sea inferred from satellite altimeter data - Ankiq Taofiqurohman; Mochamad Furqon Azis Ismail; Taslim Arifin; Handy Chandra; Kandaga Pujiana (All Earth, 2025)
The interannual variability of the mesoscale eddy field in the Banda Sea is investigated based on long-term altimetry observations covering the period from 1993 to 2022. The energy spectrum analysis indicates that annual frequency dominates the eddy kinetic energy (EKE) variation in the Banda Sea, which peaks between March and April. This study reveals notable interannual variability in mesoscale EKE within the basin, particularly along the path of the Southern Boundary Current (SBC) extension in the southwestern and central regions of the Banda Sea between 123.0°-128.0° E and 5.0°-7.0° S. During high-EKE periods, the eastward flow of the SBC intensifies, which may increase the horizontal shear of the mean flow and enhance EKE in the Banda Sea. In contrast, during low-EKE periods, the eastward flow of the SBC weakens, resulting in a decrease in EKE. Mechanism analysis suggests that EKE is consistently advected eastward by the SBC advection process during both high- and low-EKE years. This study emphasises the critical role of the SBC in redistributing interannual variability of EKE in the Banda Sea.